'4+1' Mixed Ligand Strategy for the Preparation of 99mTc‐Radiopharmaceuticals for Hypoxia Detecting Applications. Issue 10 (4th April 2017) - Vats, Kusum; Mallia, Madhava B.; Mathur, Anupam; Sarma, Haladhar D.; Banerjee, Sharmila
Abstract: The '4+1' mixed ligand strategy enables radiolabeling of biomolecules with 99m Tc at low ligand concentration without affecting it's in vivo biological activity. The '4+1' mixed‐ligand complexes consist of central Tc(III) metal atom coordinated to a tetradentate tripodal chelator 2, 2′, 2′′‐nitrilotriethanethiol (NS3 ) and a monodentate isocyanide group tethered to a biomolecule. The present work describes the use of '4+1' mixed ligand strategy to design radiopharmaceuticals for the detection of tissue hypoxia in vivo. Isocyanide derivatives of two nitroimidazoles, viz. 2‐nitroimidazole (2NimNC) and metronidazole (MetNC), were synthesized and radiolabeled with 99m Tc using '4+1' mixed ligand approach. The complexes [ 99m Tc(NS3 )(2NimNC)] and [ 99m Tc(NS3 )(MetNC)] could be prepared in excellent yield (>90%). The structure of 99m Tc‐complexes prepared at the no‐carrier‐added (nca) level was corroborated by spectroscopic analysis of corresponding rhenium analogues at the macroscopic level. Preliminary biological evaluation of the two nitroimidazole‐'4+1' mixed ligand complexes in Swiss mice bearing fibrosarcoma tumor showed uptake and retention of the complexes in tumor. Abstract : Radiolabeled nitroimidazoles are potential markers of hypoxia and offers a non‐invasive technique for the hypoxia detection. The present work describes the preparation of two 99m Tc labelled nitroimidazole derivatives using '4+1' mixed ligand strategy and their evaluation in Swiss mice bearing fibrosarcoma tumor.